Effect of substrates of transplantation of the rare epiphytic orchid Dendrobium farmeri for conservation - ANCHALEE NUAMMEE; THITIPORN PINGYOT; SIRIYAKORN FOOWAN; SUPALAK PUMIKONG; WIRATA RUJICHAIPIMON; SUJINDA SORNPOOD; PRATEEP PANYADEE (Society for Indonesian Biodiversity, 2024)
Abstract. Nuammee A, Pingyot T, Foowan S, Pumikong S, Rujichaipimon W, Sornpood S, Panyadee P. 2024. Effect of substrates of transplantation of the rare epiphytic orchid Dendrobium farmeri for conservation. Biodiversitas 25: 708-715. Dendrobium farmeri Paxton is an epiphytic orchid, one of the most celebrated for its beauty. However, its natural population is dwindling, and it faces the risk of extinction. Although tissue culture techniques are successful for orchid propagations, the transplantation of in vitro-derived plantlets to ex-vitro conditions is often restricted by high mortality, which is considered a challenging and crucial stage in orchid conservation. This study investigated the effect of substrate mixtures on the survival and growth of D. farmeri plantlets under greenhouse conditions. The substrates for acclimatization contained coconut husk, charcoal chips, brick chips, sphagnum moss, fern fiber, and leaf mold in various ratios. Survival percentage and vegetative growth characteristics of plantlets were the main observations recorded. The result showed that the substrate mixture containing brick chips, charcoal chips, and sphagnum moss in a 1:1:2 ratio was the most effective, yielding 100% at 30 days and 96.7% at 180 days post-transplantation, fostering improved development of plantlets under greenhouse conditions. The findings suggest that this optimized substrate mixture could be a standard approach for acclimating D. farmeri and potentially other epiphytic orchids, enhancing conservation efforts and commercial cultivation.